Extending beyond Policy: Reaching UNAIDS' Three "90"s in Malawi - Zengani Chirwa; Florence Kayambo; Lolade Oseni; Marya Plotkin; Cyndi Hiner; Chimwemwe Chitsulo; Kelly Curran; Kelly Curran; Thokozani Kalua; Stacie C. Stender; Stacie C. Stender (Frontiers Media S.A., 2018)
Malawi, like other countries with a generalized HIV epidemic, is striving to reach the ambitious targets set by UNAIDS known as the three 90's for testing, provision of antiretroviral therapy and viral suppression. Assisted by Malawi's progressive policies on HIV/AIDS, it appears possible that Malawi will attain these targets, but only by employing innovative program approaches to service delivery which help fill policy gaps. This article describes how a dedicated cadre of layperson testers and HIV-positive peers appears to have helped attain increases in HIV and viral load testing and retention in care in four districts in Malawi, and situates these innovations in a policy framework analysis.